2003
DOI: 10.1159/000073898
|View full text |Cite
|
Sign up to set email alerts
|

Does Treatment Modality of Intracranial Ruptured Aneurysms Influence the Incidence of Cerebral Vasospasm and Clinical Outcome?

Abstract: Background: Cerebral vasospasm is the most common cause of morbidity and mortality after aneurysmal subarachnoid hemorrhage (SAH). This study is designed to determine whether the incidence of symptomatic vasospasm and the overall clinical outcome differ between patients treated with surgical clipping compared with endovascular obliteration of aneurysms. Methods: In this prospective study, 98 patients with aneurysmal SAH were treated. Seventy-two patients underwent surgery and clipping and 26 had coil embolizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 20 publications
2
41
0
2
Order By: Relevance
“…Only four studies were prospective [5,7,9,11]. In five out of seven studies including 758 patients undergoing clipping and 249 patients undergoing coiling, no differences in terms of outcome (GOS) could be demonstrated [5,7,[9][10][11].…”
Section: Incidence Of Vasospasm and Risk Factorsmentioning
confidence: 97%
See 3 more Smart Citations
“…Only four studies were prospective [5,7,9,11]. In five out of seven studies including 758 patients undergoing clipping and 249 patients undergoing coiling, no differences in terms of outcome (GOS) could be demonstrated [5,7,[9][10][11].…”
Section: Incidence Of Vasospasm and Risk Factorsmentioning
confidence: 97%
“…The authors demonstrated that patients with better clinical grades (WFNS I-III) at hospital admission were less to suffer symptomatic CVS when treated with endovascular techniques compared with surgical treatment. More recently, Dehdashti et al [11] reported the results of a study in 72 patients, an incidence of symptomatic CVS of 25% in patients undergoing clipping and 15% in patients undergoing coiling of ruptured aneurysms. The authors found no statistical significance comparing the neurological deficits in both groups.…”
Section: Incidence Of Vasospasm and Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Se estima que en un 5-9% de los pacientes con HSA que mueren o permanecen con discapacidad severa el vasospasmo es la causa [2][3][4] .…”
Section: Introductionunclassified